THE UTTILIZATION OF JOGJA SMART SERVICE APPLICATION: AN E-READINESS APPROACH - Anggraini, Auliya Try; Iqbal, Muhammad (Journal of Governance and Public Policy, 2020)
This study will analyze the readiness of the Yogyakarta City Government in Jogja Smart Service services. This study will use the E-Readiness approach to measure government preparedness. The four indicators of the E-Readiness model are Policy, infrastructure, financial resources, and human resources. This research uses a qualitative approach. The findings show the Yogyakarta City Information and Bath Communication Office is ready in the implementation process in developing the concept of the smart city through the Jogja Smart service application. Policy readiness can be seen from the availability of the legal basis stated in Yogyakarta Mayor Regulation No. 15 of 2015 concerning e-Government and the decision of the mayor of Yogyakarta number 373 regarding the application of Jogja smart services related to the position, duties, and functions of technical managers. From the aspect of the development of Jogja Smart Service application infrastructure, it is ready to implement the application of Jogja smart service. It is intended that the infrastructure has been available from previous years. Overall readiness of musty budget resources can be seen from a very significant budget allocation from year to year where the application of these funds comes from the budget, and there is no allocation of funds from the private sector. If viewed from the aspect of internal human resources, there is still a lack of human resources in the field of programmers so that the government cooperates with programmers in developing Jogja Smart Service applications.